Spectrophotometric Determination of Zidovudine in Pharmaceuticals Based on Charge-Transfer Complexation Involving N-Bromosuccinimide, Metol and Sulphanilic Acid as Reagents - K. Basavaiah; U. R. Anil Kumar (E-Journal of Chemistry)
A simple spectrophotometric method is proposed for the determination of zidovudine(ZDV) in bulk drug and in pharmaceutical preparations. The method is based on the oxidation of ZDV by a known excess of oxidant N-bromosuccinimide (NBS), in buffer medium of pH 1.5, followed by the estimation of unreacted amount of oxidant with metol and sulphanilic acid. The reacted oxidant corresponds to the amount ZDV. The purple-red reaction product absorbs maximally at 530 nm and Beer’s law is obeyed over a range 5 to 75 μg mL-1. The apparent molar absorptivity is calculated to be 5.1×103 L mol-1cm-1, and the corresponding Sandell sensitivity value is 0.052 μg cm-2. The limit of detection and quantification are found to be 0.90 and 2.72, respectively. Intra-day and inter-day precision and accuracy of the developed methods were evaluated as per the current ICH guidelines. The method was successfully applied to the assay of ZDV in tablet/capsule preparations and the results were statistically compared with those of the reference method by applying the Student’s t-test and F-test. No interference was observed from the common tablet/capsule excipients. The accuracy of the method was further ascertained by performing recovery studies via standard-addition method.